Design, fabrication and testing of mini flexible heat pipe - Lu, Shaoning. (2008)
Prototypes of flexible heat pipes have been designed and fabricated to provide extra freedoms in bending, twisting, oscillating and deforming to overcome the constraints in the compact electronics with awkward space layout. Visualizations of the two-phase flow patterns inside the heat pipe together with the measurement of thermal performance have been conducted for the first time on flexible heat pipe. A new oscillatory mode, where wave travels periodically on the water film between the evaporator and condenser, has been identified to provide an extremely high heat transfer rate. Real time images have been recorded and analyzed to reveal the mechanism responsible for the enhanced performance. By operating the heat pipes at various power levels, degrees of bending and orientations, effects of heating power and flexibility are further established.